Southern communities : identity, conflict, and memory in the American South - Nash, Steven E.; Stewart, Bruce E.; Inscoe, John C., 1951- (The University of Georgia Press, 2019)
"Building upon recent scholarship, this anthology explores the nature of community in the American South during the long nineteenth century. The fourteen essays, written and compiled in honor of historian John C. Inscoe, define community as more than a place or a nostalgic longing for a lost way of life; instead, they view community as a web of social relationships, both voluntary and coercive. Importantly, the contributors recognize that there was never a singular Southern community. A diverse population of Southerners built a multitude of communities across the region. Neither do the contributors romanticize nineteenth-century communities, pointing out that they were often rife with discord and competition. The collected essays analyze Southern communities through identity formation, conflict, and memory. The essays in the first section chronicle the construction of four communities before and during the Civil War: the enslaved, the slaveholding, the Confederate, and the emotional. The second section includes six essays that examine the role that civil war, emancipation, and modernization played in challenging community cohesion, while the final section explores how white southerners often turned to memory and nostalgia to reconstruct communities in ways that preserved the Old South's racial and gender status quo well into the twentieth century. Stephen Berry's afterword highlights the career of John Inscoe"--